Analysis of the entrepreneurial attitude in cooperative fishing societies in Mexico - García Rodríguez, Linda; Fuentes Guevara, Darío; Pico González, Beatriz (REVESCO. Revista de Estudios Cooperativos, 2021)
The objective of this article was to know what are the subjective social norms, the attitude and personal skills and the entrepreneurial intention of the presidents of the fishing cooperatives of the Northern Zone of the State of Sinaloa, Mexico, because it was observed that depending The usufruct they receive will depend on the projects they undertake and the activities they carry out. The research was carried out through a methodology of a quantitative nature with a scope according to the level of knowledge obtained with said research: descriptive - correlational. The results obtained are outlined to what is written in the principle that cites the promotion of cooperative education and education in the solidarity economy, as well as what the literature indicates that people are capable of detecting business opportunities, having the expectation of success and assuming the risks, as well as the identity traits based on communicative factors, cohesion and social relations based mainly on cooperation and solidarity; on the other hand, the affirmation is supported that the viability not only depends on the collective undertaking, but on finding the minimum socio-economic conditions that make it possible.
Keywords: Fishing cooperatives; Entrepreneurial Intention; Attitude; Subjective social norms; Personal skills